PENDAMPINGAN PEMANFAATAN LIMBAH MINYAK GORENG MENJADI SABUN DAN LILIN PADA MASYARAKAT BUKIT DEWA RESIDENCE KOTA BENGKULU - Deni Agus Triawan; Ria Nurwidiyani; Morina Adfa; Muhammad Alvin Reagen (Universitas Mataram, 2022)
Waste cooking oil is one of the sources of environmental pollutants from the household sector which, if discharged into the environment, it can pollute the environment. Therefore, alternative processing of cooking oil waste is needed into a valuable product and of course can overcome environmental pollution. One alternative that can be chosen is the manufacture of soap and candles based on the presence of fatty acids derived from vegetable oils. Community service activities about making soap and wax from used cooking oil aim to increase the use value and economic value of used cooking oil waste which has not been utilized and even becomes waste that can pollute the environment. This activity was carried out in the Bukit Dewa Residence Residential community in Bengkulu City with 15 participants consisting of housewives. This activity was carried out by several methods, namely the delivery of information, discussions and questions and answers as well as product manufacturing practices and training. Based on the activities carried out, it can be seen that this activity is going well. This is shown by the enthusiasm of the community when delivering information, discussions, questions and answers as well as very good practice and training activities. Evaluation of the success of service activities is known by reviewing the stage of understanding before and after the activity. The achievement indicator is a change in public understanding before and after the activity about making soap from cooking oil waste. Before the activity, 80-90% of participants did not know and after the activity all participants knew the process of making soap and wax from waste cooking oil. This activity is expected to have a significant impact on the cooking oil waste processing sector in the community which can reduce the risk of environmental pollution and provide economic value for the community.